Asset Pricing with Spatial Interaction - Kou, Steven; Peng, Xianhua; Zhong, Haowen (Management Science, 2018)
We propose a spatial capital asset pricing model and a spatial arbitrage pricing theory (S-APT) that extend the classical asset pricing models by incorporating spatial interaction. We then apply the S-APT to study the comovements of eurozone stock indices (by extending the Fama–French factor model to regional stock indices) and the futures contracts on S&P/Case–Shiller Home Price Indices; in both cases, spatial interaction is significant and plays an important role in explaining cross-sectional correlation. The e-companion is available at https://doi.org/10.1287/mnsc.2016.2627 . This paper was accepted by Neng Wang, finance.